2009
DOI: 10.1074/jbc.m109.042671
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 and Interleukin-6 Promote Survival of Human CD11b+ Peripheral Blood Mononuclear Cells and Induce M2-type Macrophage Polarization

Abstract: CCL2 and interleukin (IL)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
393
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 499 publications
(420 citation statements)
references
References 50 publications
(91 reference statements)
21
393
1
5
Order By: Relevance
“…5B). All four chemokines promote M2 protumor polarization of macrophages (23)(24)(25)(26). Thus, our gene-expression analysis suggests that loss of Ptprd in the tumor cells might lead to the activation of genetic programs that affect the immune response, and in particular macrophages.…”
Section: Heterozygous Loss Of Ptprd Results In P-stat3 Accumulation Andmentioning
confidence: 78%
“…5B). All four chemokines promote M2 protumor polarization of macrophages (23)(24)(25)(26). Thus, our gene-expression analysis suggests that loss of Ptprd in the tumor cells might lead to the activation of genetic programs that affect the immune response, and in particular macrophages.…”
Section: Heterozygous Loss Of Ptprd Results In P-stat3 Accumulation Andmentioning
confidence: 78%
“…The activation of MCP-1 is driven by hyperglycaemia and glomerular hemodynamic perturbations in diabetes mellitus, and is an important target in the progression of diabetic nephropathy 167 . Some investigations have suggested that MCP-1 favors a shift from M1 macrophages to M2 macrophages in human macrophages 168,169 , and macrophage polarization has been shown to shift from an M1 phenotype in the early phase of diabetes mellitus to an M2 phenotype in the later phases of the disease in an experimental animal model 170 . Thus, the inhibition of MCP-1 signaling seems to be beneficial in the treatment of diabetic nephropathy 170 .…”
Section: [H2] Influence Of Chemokinesmentioning
confidence: 99%
“…210 IL6, among other pro-inflammatory cytokines, has also been implicated in the development of a cachectic conditions in skeletal muscles 211 and is also responsible for activation of autophagy in cell culture models. 212 We propose that recovery from and adaptation to exercise represents a single, unified physiological response resulting from cooperation between autophagy and the heat shock response, 2 protein management systems. In this model, the initial phase of exercise-induced damage activates protein turnover to recycle and reclaim amino acids and to remove damaged proteins.…”
Section: Exercise As a Modelmentioning
confidence: 99%